2019
DOI: 10.1007/s10008-018-04174-5
|View full text |Cite
|
Sign up to set email alerts
|

Applications of carbon in lead-acid batteries: a review

Abstract: A review presents applications of different forms of elemental carbon in lead-acid batteries. Carbon materials are widely used as an additive to the negative active mass, as they improve the cycle life and charge acceptance of batteries, especially in high-rate partial state of charge (HRPSoC) conditions, which are relevant to hybrid and electric vehicles. Carbon nanostructures and composite materials can also play such a role. The positive active mass additions are generally less beneficial than the negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 57 publications
0
38
0
Order By: Relevance
“…It has been confirmed that sulfation plays a greater role in the failure of lead-acid batteries as about 70 % of "dead" batteries due to deterioration in use, recovered their performance to an almost similar state to that of new ones by the use of additives, which act on the negative electrodes [2], [18]. It has been reported [14], [19]- [28] that the addition of some form of carbon to the negative electrode helps to reduce the negative effects of sulfation and also boosts the charge acceptance rates of lead-acid batteries.…”
Section: Photovoltaic Systemmentioning
confidence: 93%
“…It has been confirmed that sulfation plays a greater role in the failure of lead-acid batteries as about 70 % of "dead" batteries due to deterioration in use, recovered their performance to an almost similar state to that of new ones by the use of additives, which act on the negative electrodes [2], [18]. It has been reported [14], [19]- [28] that the addition of some form of carbon to the negative electrode helps to reduce the negative effects of sulfation and also boosts the charge acceptance rates of lead-acid batteries.…”
Section: Photovoltaic Systemmentioning
confidence: 93%
“…In comparison, PANI/Cu-Pp/CNTs have the highest conductivity due to the fast electron delocalization along the PANI because of the combination of Zn-Pp and CNTs [34][35][36][37] . .…”
Section: Effects Of Pani/cu-pp/cnts On the Corrosion Ratementioning
confidence: 99%
“…In contrast, the relaxation period may last hours, and thus may provide sufficient data for this purpose. The problems of the modern technology used in the battery production process were considered in [24]. Carbon materials are widely used as an additive to the negative active mass and allow the battery specific energy and active mass utilization to be increased.…”
Section: Introductionmentioning
confidence: 99%